Integration of International, National and Madrasah Curriculum to Improve the Quality of Graduates At Mi Muslimat NU Pucang Sidoarjo - Solichati Solichati; Musfiqon Musfiqon (Proceedings of The ICECRS, 2021)
The research has purpose to know the implementation of integration the international, national, and madrasah curriculum in MI Muslimat NU Pucang Sidoarjo. The policies carried out by the head of madrasah through preparation of RKM, fulfillment of eight SNPs, division of job discribtion, providing guidance to educators and education staff in conducting supervision that programmed well. The implementation of integrating of third curriculum carried out by adopting Mathematic, English and Science subjects from the Cambridge University international curriculum and adapting general subjects from the national curriculum 2018 revision of the Ministry of Education and Culture and religious subjects al- Qur'an Hadith, Aqidah akhlaq, Fiqh, SKI and Arabic madrasah curriculum from the Ministry of Religion through the development the forms of learning processing and classroom, Development of the PAIKEM learning model, self-development program and evaluation. The quality of graduates after the implementation of integration the international, national and madrasah curriculum in MI Muslimat NU Pucang Sidoarjo accepted in the favorite of SMP/MTS which are evidenced with the results of SKHUN, UN, UAMBD and Check Point. The result of the research show that integration of international, national, and madrasah curriculum has been running as it should,